Pelatihan Pemanfaatan Sampah Organik Sebagai Bahan Eco-Enzym Untuk Pembuatan Pupuk Cair, Desinfektan Dan Hand Sanitizer - Vonny Indah Sari; Neng Susi; Muhammad Rizal (Asosiasi Dosen Akuntansi Indonesia, 2021)
Garbage is one of the phenomena in Pekanbaru City. Almost in every housing on the roadside of Pekanbaru City, garbage piles up and causes discomfort. Handling waste is the task of the Pekanbaru city government that must be considered better. Most of the waste that becomes waste is organic waste. Based on the findings at the location, and based on the results of interviews conducted with the local community, data obtained that the local community has never received training to improve skills in the use of organic waste as an Eco-Enzym maker. This community dedication activity aims to obtain alternative natural products as hand sanitizers, disinfectants, and organic fertilizers during the COVID-19 pandemic and reduce the impact of environmental pollution. The implementation method begins with data and information collection, team and partner coordination, preparation stage and training activities for partners. Innovation and creativity in the manufacture of eco-enzymes are present as the best solution for housewives in processing organic waste into more useful products. Through this activity, it is hoped that housewives can be more creative and innovative in processing household waste in the future. The results of this activity showed that there was an increase in public knowledge about processing waste into more useful products such as eco-enzymes. The results of the questionnaires that were distributed showed that the increase in participants' knowledge increased by 100% after the training was carried out